Does CEO Duality and Family Ownership Concentration Hinder the Effectiveness of the Corporate Board of Directors in Jordanian Service Firms? - Daoud, Khaldoon Ahmad Al; Al-Sraheen, Dea'a Al-Deen Omar; Aleqab, Mahmoud Mohmad (Journal of Environmental Accounting and Management, 2026)
The purpose of this paper is to investigate the effects of CEO duality and family ownership concentration on the effectiveness of the board of directors in a sample of Jordanian services firms. This study used a sample of 67 services firms listed on the Amman Stock Exchange (ASE) over the four years from 2013 to 2016 (N = 268 firms). A composite proxy for board effectiveness ranging from 0 to 3 using board size, board independence and the frequency of board meeting was utilized. The results indicate that the combined role of CEO and the chairman of the board and a high level of family ownership concentration weakens board effectiveness, which, in turn, hinders the monitoring function of corporate boards. This study contributes to the current literature related to the corporate governance structure in emerging capital markets like Jordan in proposing a model that may ensure the effective monitoring function of corporate boards.